2007
DOI: 10.1681/asn.2007040440
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Kidney Injury Following Oral Phosphosoda Bowel Preparations

Abstract: Case reports and case series suggest a potential link between oral sodium phosphosoda used in preparation for outpatient colonoscopy and kidney injury, but controlled studies are lacking. We performed a case-control study nested within a cohort of patients with baseline serum creatinine Յ1.5 mg/dL who underwent outpatient colonoscopy. We defined a case of kidney injury as a rise in serum creatinine Ն0.5 mg/dL and/or 25% between values obtained during the 6 months prior and during the 6 months following colonos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
51
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 28 publications
2
51
0
3
Order By: Relevance
“…16 Most of our present information on phosphate nephropathy derives from case series and retrospective epidemiologic analyses. 11,14,[17][18][19] Moreover, there is no specific therapy for established phosphate nephropathy.…”
mentioning
confidence: 99%
“…16 Most of our present information on phosphate nephropathy derives from case series and retrospective epidemiologic analyses. 11,14,[17][18][19] Moreover, there is no specific therapy for established phosphate nephropathy.…”
mentioning
confidence: 99%
“…But it has the potential for acute kidney injury called APN. 1 The incidence of APN remains unknown and it can occur even with normal renal function.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 The literature also confirms that patients prefer lower volume solutions related to their being more comfortable and tolerable. 7,11 With the issue of FDA regulatory warnings on the use of Fleets Phospho-soda in bowel preparation, [12][13][14] interest has increasingly shifted to the use of MiraLAX (polyethylene glycol 3350 powder) in combination with Gatorade as an alternative to well-established polyethylene glycol solutions such as Golytely (4 L PEG 3350 electrolyte solution) MiraLAX is FDA approved for constipation and has also been studied in paediatric chronic constipation. [15][16][17] A small, single-arm community-based study of 29 patients who underwent colonoscopy with a MiraLAX ⁄ Gatorade preparation reported that it was efficacious, safe and well tolerated by patients.…”
Section: Introductionmentioning
confidence: 99%